Analysis of the Needs of the PMRI Learning Environment for Geometry Material on the Critical Thinking Ability of PGSD Students - Mulbasari, Anggria Septiani; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Aisyah, Nyimas (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Conducive learning situation is related to the quality of learning that is packaged in a learning environment. The purpose of this study is to describe the analysis of the PMRI learning environment's needs for geometry material on critical thinking skills. The ability to think critically is a skill that must be possessed by teachers, prospective teachers, and students in the 21st century; therefore, the availability of a learning environment based on the PMRI approach is very important for teachers, prospective teachers, and students, especially prospective teachers. This study uses a quantitative descriptive research method, with the number of respondents specifically testing the critical thinking ability test questions 40 people who were PGSD students at the PGRI Palembang University and the number of respondents specifically filling out the questionnaire as many 199 people, consisting of students from PGRI University of Palembang, PGRI University of Silampari and PGRI University of Yogjakarta. Data was gathered through the use of tests and questionnaires. The data collected were analyzed descriptively and quantitatively. Based on the analysis of test data, 80% of critical thinking skills are still below average, and questionnaire analysis revealed that 60.9% of the geometry material is considered difficult for students; students also do not understand the knowledge of 21st century skills, especially critical thinking skills, and the PMRI approach is still not well applied in the student learning environment. Therefore, requires further research that applies the PMRI approach in the learning environment and geometric difficulties can be overcome.